The Potential of Mesenchymal Stromal Cell as Therapy in Neonatal Diseases - Liau, Ling Ling; Al-Masawa, Maimonah Eissa; Koh, Benson; Looi, Qi Hao; Foo, Jhi Biau; Lee, Sau Har; Cheah, Fook Choe; Law, Jia Xian (Frontiers in Pediatrics, 2020)
Mesenchymal stromal cells (MSCs) can be derived from various tissue sources, such as the bone marrow (BMSCs), adipose tissue (ADSCs), umbilical cord (UC-MSCs) and umbilical cord blood (UCB-MSCs). Clinical trials have been conducted to investigate the potential of MSCs in ameliorating neonatal diseases, including bronchopulmonary dysplasia (BPD), intraventricular haemorrhage (IVH) and necrotizing enterocolitis (NEC). In preclinical studies, MSC therapy has been tested for the treatment of various neonatal diseases affecting the heart, eye, gut and brain as well as sepsis. Up to date, the number of clinical trials using MSCs to treat neonatal diseases is still limited. The data reported thus far positioned MSC therapy as safe with positive outcomes. However, most of these trials are still preliminary and generally smaller in scale. Larger trials with more appropriate controls and a longer follow-up period need to be conducted to prove the safety and efficacy of the therapy more conclusively. This review discusses the current application of MSCs in treating neonatal diseases, its mechanism of action and future direction of this novel therapy, including the potential of using MSC-derived extracellular vesicles instead of the cells to treat various clinical conditions in the newborn.